2023
DOI: 10.7717/peerj.15283
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, genetic diversity, and antimicrobial resistance profiles of Vibrio parahaemolyticus in seafood in Bangkok and eastern Thailand

Chartchai Changsen,
Somsak Likhitrattanapisal,
Kamonwan Lunha
et al.

Abstract: Background Emergence of Vibrio parahaemolyticus pandemic strain O3:K6 was first documented in 1996. Since then it has been accounted for large outbreaks of diarrhea globally. In Thailand, prior studies on pandemic and non-pandemic V. parahaemolyticus had mostly been done in the south. The incidence and molecular characterization of pandemic and non-pandemic strains in other parts of Thailand have not been fully characterized. This study examined the incidence of V. parahaemolyticus in seafood samples purchased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Available literature also suggests a high resistance prevalence towards β-lactams, which we phenotypically confirmed in this study by the resistance of all three strains towards ampicillin and piperacillin. Larger-scale ( n > 36) phenotypical studies are confirming this too, with high reported resistance prevalence towards both penams [ e.g., 45–100% to ampicillin [ 6 , 28 , 30 33 ] and 68–100% to penicillin [ 30 32 ]] and cephalosporins [ e.g., 49.6–84% to cefazolin [ 31 , 34 ], 52–73% to cefotaxime [ 33 , 35 ] and 24–82% to cephalothin [ 30 , 34 ]].…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Available literature also suggests a high resistance prevalence towards β-lactams, which we phenotypically confirmed in this study by the resistance of all three strains towards ampicillin and piperacillin. Larger-scale ( n > 36) phenotypical studies are confirming this too, with high reported resistance prevalence towards both penams [ e.g., 45–100% to ampicillin [ 6 , 28 , 30 33 ] and 68–100% to penicillin [ 30 32 ]] and cephalosporins [ e.g., 49.6–84% to cefazolin [ 31 , 34 ], 52–73% to cefotaxime [ 33 , 35 ] and 24–82% to cephalothin [ 30 , 34 ]].…”
Section: Discussionmentioning
confidence: 73%
“…This is again reflected in phenotypical studies on V. parahaemolyticus clinical and environmental strains, where low prevalence of resistance towards tetracyclines [ e.g,. 0.3% to doxycycline [ 30 , 31 , 36 ], 0–15% to tetracycline [ 27 , 28 , 30 33 , 35 , 36 ]], trimethoprim-sulfamethoxazole [0–7% [ 27 , 30 , 31 , 33 ]], and fluoroquinolones ( e.g,. 0% to ciprofloxacin [ 27 , 30 ] and 0–1% to levofloxacin [ 27 , 33 ]] were reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations